Advances in crosslinking strategies of biomedical hydrogels. (16th January 2019) - Hu, Weikang; Wang, Zijian; Xiao, Yu; Zhang, Shengmin; Wang, Jianglin
Abstract : This review presents the commonly used crosslinking methods for hydrogel synthesis and summarizes the current status and discusses future perspectives. Abstract : Biomedical hydrogels as sole repair matrices or combined with pre-seeded cells and bioactive growth factors are extensively applied in tissue engineering and regenerative medicine. Hydrogels normally provide three dimensional structures for cell adhesion and proliferation or the controlled release of the loading of drugs or proteins. Various physiochemical properties of hydrogels endow them with distinct applications. In this review, we present the commonly used crosslinking method for hydrogel synthesis involving physical and chemical crosslinks and summarize their current progress and future perspectives.